2005
DOI: 10.1128/iai.73.4.2367-2378.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of theEscherichia coliO157:H7(pO157)ecfOperon and Lipid A Myristoyl Transferase Activity in Bacterial Survival in the Bovine Gastrointestinal Tract and Bacterial Persistence in Farm Water Troughs

Abstract: Escherichia coli O157:H7 is an important food-borne pathogen that causes hemorrhagic colitis and the hemolytic-uremic syndrome in humans. Recently, we reported that the pO157 ecf (E. coli attaching and effacing gene-positive conserved fragments) operon is thermoregulated by an intrinsically curved DNA and contains the genes for bacterial surface-associated proteins, including a second copy of lipid A myristoyl transferase, whose chromosomal copy is the lpxM gene product. E. coli O157:H7 survives and persists w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 61 publications
2
34
1
Order By: Relevance
“…Its product is similar to that of the chromosomal gene lpxM. Deletion of both genes leads to reduced survival in the bovine GIT and reduced persistence in water troughs (68). Deletion of toxB results in reduced adherence to cultured epithelial cells and influenced the expression and secretion of proteins encoded by LEE but did not affect the colonization of E. coli O157:H7 in calves (60,62).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Its product is similar to that of the chromosomal gene lpxM. Deletion of both genes leads to reduced survival in the bovine GIT and reduced persistence in water troughs (68). Deletion of toxB results in reduced adherence to cultured epithelial cells and influenced the expression and secretion of proteins encoded by LEE but did not affect the colonization of E. coli O157:H7 in calves (60,62).…”
Section: Discussionmentioning
confidence: 84%
“…Three of four steers given E. coli O157:H7 continued to be culture positive on day 32, whereas only one of four steers given E. coli K-12 continued to be culture positive on day 25 and all four animals in this group eliminated the E. coli K-12 by day 32 (Fig. 1) (57,58,68), and showed a distinct colonization pattern compared with the nonpathogenic E. coli K-12.…”
Section: Confirmation Of Gene Deletion and Po157-cured Strainsmentioning
confidence: 99%
“…In addition, WabB shows a UDP-Nacetylglucosamine : (heptose) LPS a-1,7-N-acetylglucosamine transferase that is responsible for a non-stoichiometric Nacetylglucosamine substitution in the heptose-III residue (Kaniuk et al, 2004). Therefore, the shf locus seems to be a module involved in O157 LPS lipid A-core modifications, and is also suggested to play a role in the survival and persistence of E. coli O157 : H7 in cattle and in the environment (Yoon et al, 2005).…”
Section: Possible Role Of the Petn Moiety In Lipid A-lipid A Moleculamentioning
confidence: 99%
“…pO157, a 92-kb F-like plasmid, is found almost invariably in all E. coli O157:H7 clinical isolates (18) and shares sequence similarities with plasmids present in other EHEC serotypes (15,23). A number of virulence factors encoded by pO157, including an enterohemolysin (ehxA), a type II secretion system, a serine protease (espP), a catalase-peroxidase (katP), a potential adhesin (toxB), a Cl esterase inhibitor (stcE), and attaching and effacing gene-positive conserved fragments (ecf), were identified (2,25). ecf encodes a functional LpxM homologue that catalyzes the addition of myristate to the lipid A moiety of lipopolysaccharide (LPS) (25).…”
mentioning
confidence: 99%
“…A number of virulence factors encoded by pO157, including an enterohemolysin (ehxA), a type II secretion system, a serine protease (espP), a catalase-peroxidase (katP), a potential adhesin (toxB), a Cl esterase inhibitor (stcE), and attaching and effacing gene-positive conserved fragments (ecf), were identified (2,25). ecf encodes a functional LpxM homologue that catalyzes the addition of myristate to the lipid A moiety of lipopolysaccharide (LPS) (25). Earlier plasmid-profiling studies showed the variable presence in O157:H7 isolates of, in addition to pO157, several plasmids ranging from 2 to 6 kb (19,21).…”
mentioning
confidence: 99%